(untitled) (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
Safflower (Carthamus tinctorius L.) is widely used in the treatment of cardiovascular diseases. Research has shown that safflower possesses significant biological activity, including inhibition of platelet aggregation, protection against myocardial ischemia, immune modulation, and antioxidant effects. Therefore, the objective of this study was to evaluate the effects of an injectable formulation derived from Carthamus tinctorius L. on cardiovascular function. Particular attention was given to the manifestation of these effects in clinical symptoms and the diagnostic value of electrocardiographic (ECG) analysis. For the experiment, an iWire-RX834-BIO4 ECG reader (iWorX Inc., USA) was used in conjunction with male BALB/c mice (n = 9), aged 6–8 weeks. The animals were divided into four groups: a healthy group (0.9% NaCl, n = 3), a negative control group (10% CaCl₂, 160 mg/kg, n = 3), a treatment group (Gurgem injection, 2.1 ml/kg, n = 3), and a positive control group (Verapamil injection). Differences between the groups were assessed based on changes in heart rate and specific ECG parameters (heart rate, R-R interval, and QT interval). ECG recordings were obtained for 20 minutes for all animals. The average heart rate in the healthy group was 410 bpm. In contrast, the negative control group exhibited a 14.1% increase in heart rate, indicating tachycardia. However, in the treatment group receiving Gurgem injection, the average heart rate was 18.7% lower than that of the negative control group. Tachyarrhythmia is typically characterized by a shortened R-R interval, which can be detected via ECG. In the positive control group, the average R-R interval was 141.1 ms, whereas in the negative control group, it was reduced to 133.6 ms, reflecting a 5.2% decrease. In the treatment group, the R-R interval was extended by 20.8% compared to the negative control group, suggesting a positive modulatory effect on cardiac rhythm and tachycardia. In conclusion, the injectable formulation derived from Carthamus tinctorius L. demonstrated therapeutic effects in an experimental model of arrhythmia (tachycardia), including stabilization of cardiac rhythm and reduction of heart rate.